'Attempting to deal with the past': historical inquiries, legacy prosecutions, and Operation Banner. (4th July 2021) - Sanders, Andrew
ABSTRACT: Over the summer of 2019 a number of maroon banners appeared across towns and cities in Northern Ireland, declaring that the local population 'stands with Soldier F'. Soldier F was a member of the Parachute Regiment who, in March of 2019, was charged with the murders of James Wray and William McKinney and five additional attempted murders as a result of his actions on Bloody Sunday, 30 January 1972. These charges were announced at a time when it was reported that up to 200 former members of the British Army could face official investigation for their conduct in Northern Ireland. These cases sit at the centre of the sensitive and divisive issue of the legacy dimension of the Northern Ireland conflict, posing a challenge to the continuing success of the Northern Ireland peace process. Engaging a developing literature on post conflict reconciliation processes, this article will analyse the issue of legacy prosecutions from Operation Banner.